2017
DOI: 10.11604/pamj.2017.28.131.10480
|View full text |Cite
|
Sign up to set email alerts
|

Low humoral responses to human cytomegalovirus is associated with immunological treatment failure among HIV infected patients on highly active antiretroviral therapy

Abstract: Human cytomegalovirus (HCMV) is one of the opportunistic infections associated with significant morbidity and mortality among HIV/AIDS patients especially before introduction of antiretroviral therapy (ART). Little is known regarding the humoral immune response against HCMV in relation to CD4 counts among HIV infected individuals. A total of 90 achieved sera from HIV infected patients attending Bugando Medical centre care and treatment centre (CTC) aged 18 years and above were retrieved and analyzed. Sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Overwhelming evidence suggests that perinatal viral infections are common in resource-constrained countries and significantly contribute to the adverse pregnancy outcomes [ 4 , 5 , 6 , 7 , 8 ]. Rubella virus (RV), human cytomegalovirus (HCMV), dengue virus (DENV) and Zika virus (ZIKV) are endemic in the tropical regions and have been fairly studied in different populations in the study setting, with IgG seroprevalence of RV and HCMV of more than 90% being reported among general pregnant women [ 9 , 10 , 11 , 12 , 13 , 14 ]. Recently, in a study involving 8 districts, the seroprevalence of CHIKV, DENV and ZIKV were 28%, 16.1% and 6.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Overwhelming evidence suggests that perinatal viral infections are common in resource-constrained countries and significantly contribute to the adverse pregnancy outcomes [ 4 , 5 , 6 , 7 , 8 ]. Rubella virus (RV), human cytomegalovirus (HCMV), dengue virus (DENV) and Zika virus (ZIKV) are endemic in the tropical regions and have been fairly studied in different populations in the study setting, with IgG seroprevalence of RV and HCMV of more than 90% being reported among general pregnant women [ 9 , 10 , 11 , 12 , 13 , 14 ]. Recently, in a study involving 8 districts, the seroprevalence of CHIKV, DENV and ZIKV were 28%, 16.1% and 6.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%